The Tehran initiative - Rosenberg, Joel C., 1967- (Tyndale House Publishers, 2011)
With the stakes high and few viable options left, the president of the United States orders CIA operative David Shirazi and his team to track down and sabotage Iran's nuclear warheads before Iran or Israel can launch a devastating first strike.